Part-out-based spares provisioning management: A military aviation maintenance case study. Issue 1 (4th March 2014) - Block, Jan; Ahmadi, Alireza; Tyrberg, Tommy; Söderholm, Peter
Abstract : Purpose: – The purpose of this paper is to present the prerequisites for a part-out-based spares provisioning (PBSP) programme during the phase-out of an aircraft fleet. Furthermore, associated key decision criteria are identified and a framework for the phase-out management process is presented. Design/methodology/approach: – Once a decision has been taken to phase-out an aircraft fleet, a number of routines for operations, maintenance and storage are affected and new tasks and functions must be introduced before initiating the actual parting-out process. A decision-making system and a management framework is needed to manage spares planning during the end-of-life phase to ensure availability at minimum cost and to ensure a manageable risk of backorders. Findings: – For PBSP programme during the phase-out of an aircraft fleet to succeed and be cost-effective, a number of linked processes, tasks and decisions are required, e.g., those included in the framework proposed in this paper (see Figure 3). A successful implementation of PBSP also requires that these processes and tasks are carried out in a timely manner and that the communications between the concerned parties are prompt, clear and direct. One experience from the studied case is that close and trustful contacts and cooperation between the operator and maintenance provider(s) will greatly facilitate the process. Originality/value: – Although the PBSP method is fairly commonly applied within both the military and the civilian sector, somewhat surprisingly very literature has been published on the subject. Indeed, remarkably little has been published on any aspects of maintenance during the end-of-life period.